Estudo cefalométrico de indivíduos com síndrome da apneia hipopneia obstrutiva do sono - Marques, Caroline Gabriele (2006)
This study aims to identify associated characteristics of craniofacial skeletal and pharyngeal soft tissues, in lateral cephalometric teleradiography and their possible association with clinical and polyssonographic findings, observing anatomical areas which most influenced the upper airway obstruction. To evaluate a predicting cephalometric pattern for Sleep Apnea Hipopnea Obstructive Syndrome (SAHOS), a sample of 40 subjects was divided into two experimental groups: patients with mild to moderate and severe SAHOS, previously submitted to polyssonographic study, according to their Apnea or Hipopnea Índex (AHI), comparing them with a control group, 10 subjects, with no sleep disorder. The first experimental group had an AHI=15 <30 (moderate sleep apnea). The second group, an AHI> or = 30 (severe sleep apnea). After the results and the statistical methods used to compare the different studied groups, the conclusion was that the SAHOS patients when compared with the control group presented: some positional alterations in their skeletal anatomical structures, mainly a lowering of the hyoide bone in relation to the cervical vertebrae; mandilbular retrusion, increased dimensions of the pharyngeal soft tissues, increased length and width of the soft palate with a decrease of the posterior and superior airway space.